Direct comparison of mid-regional pro-atrial natriuretic peptide with N-terminal pro B-type natriuretic peptide in the diagnosis of patients with atrial fibrillation and dyspnoea. Issue 20 (3rd August 2012) - Eckstein, Jens; Potocki, Mihael; Murray, Karsten; Breidthardt, Tobias; Ziller, Ronny; Mosimann, Tamina; Klima, Theresia; Hoeller, Rebeca; Moehring, Berit; Sou, Seoung Mann; Rubini Gimenez, Maria; Morgenthaler, Nils G; et al.
Abstract : Objectives: Due to different release mechanisms, mid-regional pro-atrial natriuretic peptide (MR proANP) may be superior to N-terminal pro-B-type natriuretic peptide (NT proBNP) in the diagnosis of acute heart failure (AHF) in patients with atrial fibrillation (AF). We compared MR proANP and NT proBNP for their diagnostic value in patients with AF and sinus rhythm (SR). Design: Prospective cohort study. Setting: University hospital, emergency department. Patients: 632 consecutive patients presenting with acute dyspnoea. Main outcome measures: MR proANP and NT proBNP plasma levels were determined. The diagnosis of AHF was adjudicated by two independent cardiologists using all available data. Patients received long-term follow-up. Results: AF was present in 151 patients (24%). MR proANP and NT proBNP levels were significantly higher in the AF group compared with the SR group (385 (258–598) versus 201 (89–375) pmol/l for MR proANP, p<0.001 and 4916 (2169–10285) versus 1177 (258–5166) pg/ml, p<0.001 for NT proBNP). Diagnostic accuracy in AF patients was similar for MR proANP (0.90, 95% CI 0.84 to 0.95) and NT proBNP (0.89, 95% CI 0.81 to 0.96). Optimal cut-off levels in AF patients were significantly higher compared with the optimal cut-off levels for patients in SR (MR proANP 240 vs 200 pmol/l; NT proBNP 2670 vs 1500 pg/ml respectively). After adjustment in multivariable Cox proportional hazard analysis, MR proANP strongly predicted one-year all-cause mortality (HR=1.13 (1.09–1.17), per 100 pmol/l increase, p<0.001). Conclusion: In AF patients, NT proBNP and MR proANP have similar diagnostic value for the diagnosis of AHF. The rhythm at presentation has to be taken into account because plasma levels of both peptides are significantly higher in patients with AF compared with SR.